IDENTIFICATION OF THREATS TO THE CUSTOMS SECURITY OF THE STATE - ZAMASLO, Olga; PIDKHOMNYI, Oleg; PETYK, Marta (Scientific journal «World of Finance», 2020)
Introduction. The rapid revitalization of integration processes worldwide, the strengthening of international economic cooperation, the intensification of export-import operations increase the impact of the customs system on the state of the national economy. Therefore, there is an urgent need to use effective mechanisms of blocking and elimination of factors that undermine the customs of customs in order to comprehensively evaluate the effectiveness of the customs system and improve the level of customs security of the state. Purpose is assessing Ukraine’s customs security indicators and identification of sources of customs danger, clarification of the role and assessment of fiscal efficiency of customs authorities in ensuring the customs security of the state, development of recommendations on elimination of the main customs threats in the context of minimization of customs risks in the context of conflict of interests of individual participants of foreign economic relations. Results. The essence of the customs security of the state is revealed, the sources and threats to the customs security are identified. The importance of the indicators of the customs security of Ukraine through the prism of the customs load on the economy of the country and the efficiency of the activity of the customs authorities during 2009–2018 are analyzed. At the same time, it should be noted that the dependence of the state budget on 2/5 of the amount of customs payments is a separate risk from the point of view of the financial security of the state. It is established that the system of customs control, first of all, is characterized by qualitative output parameters, which for the most part are outside the direct jurisdiction of the customs authorities, but which directly affect the effectiveness of the customs administration in practice. The subjective factors influencing the efficiency of the customs administration are the level of information and technical support and the procedure for the organization of customs control procedures, time spent on customs clearance of goods, the establishment of communication relations between the customs relations, the level of qualification of employees and the knowledge and observance of all participants of the FEA and customs clearance procedures. It is confirmed that the main criteria for assessing the customs security of the state should be the completeness of payment of customs duties and the frequency of detection of cases of customs offenses. VAT reimbursement for bogus exports. The customs security of the state is closely related to the customs security of the subjects of foreign economic activity when crossing the goods across the customs border and is determined by the level of well-established interaction of all subjects of customs relations. Conclusion. Proposals for implementation of priority measures in the system of improving the customs security of Ukraine are substantiated and they include coordination of actions of all state bodies on the implementation of customs control in order to eliminate the corruption component during the passage of customs and border clearance, modernization of information support and communication between employees of the customs authorities and entities activities